CENP-E is an essential kinetochore motor in maturing oocytes and is masked during Mos-dependent, cell cycle arrest at metaphase II - Duesbery, Nick S. (The National Academy of Sciences of the USA, 1997)
CENP-E, a kinesin-like protein that is known to associate with kinetochores during all phases of mitotic chromosome movement, is shown here to be a component of meiotic kinetochores as well. CENP-E is detected at kinetochores during metaphase I in both mice and frogs, and, as in mitosis, is relocalized to the midbody during telophase. CENP-E function is essential for meiosis I because injection of an antibody to CENP-E into mouse oocytes in prophase completely prevented progression of those oocytes past metaphase I. Beyond this, CENP-E is modified or masked during the natural, Mos-dependent, cell cycle arrest that occurs at metaphase II, although it is readily detectable at the kinetochores in metaphase II oocytes derived from mos-deficient (MOS(−/−)) mice that fail to arrest at metaphase II. This must reflect a masking of some CENP-E epitopes, not the absence of CENP-E, in meiosis II because a different polyclonal antibody raised to the tail of CENP-E detects CENP-E at kinetochores of metaphase II-arrested eggs and because CENP-E reappears in telophase of mouse oocytes activated in the absence of protein synthesis.